Criminal Law Enforcement Against Press Crimes in Reporting Suicide Cases in the Mass Media - Melisnawati, Melisnawati; Wardana, Khristyawan Wisnu; Bone, Sholihin (Jurnal Cakrawala Hukum, 2024)
The Indonesian Constitution guarantees freedom of the press, which is part of human rights in national and democratic life. The press has an important function that influences social, economic, political, and cultural life, namely as a medium of information. Restrictions on press freedom must be firmly and clearly stipulated by laws and regulations with provisions, one of which is the regulation of press crimes in criminal law. Suicide cases are one of the cases that are widely reported by the mass media; In covering suicide cases, ideally journalists have sensitivity and can empathize by protecting the identity of the perpetrator and the family of the suicide perpetrator in accordance with Press Council Regulation Number: 2/Peraturan-DP/III/2019 Concerning Guidelines for Reporting Related to Acts and Attempted Suicide which was stipulated in Jakarta on March 22, 2019. Seeing this phenomenon, it is important to enforce the law against media that violate the rules in reporting suicide cases.